Personal Economic Worries in Response to COVID-19 Pandemic: A Cross Sectional Study - Bou-Hamad, Imad; Hoteit, Reem; Harajli, Dunia; Reykowska, Dorota (Frontiers in Psychology, 2022)
Objectives: The emergence of the COVID-19 pandemic worsened Lebanon’s economic situation and generated worries about living conditions. This study aimed to explain personal economic worries patterns among Lebanese young adults while accounting for demographics and mental health characteristics. Methods: A total sample of 988 Lebanese responses were collected, using an online survey. The analysis was conducted using regression-based methods. Results: Men exhibited higher economic worries than women. Lower levels of economic worries among people with higher wages were more pronounced. Lebanese retirees experience the highest economic worries compared to other employment status groups. Individuals with higher life satisfaction are less concerned about the economy. Mental well-being factors were positively with personal economic worries. Conclusions: The current study presents a seminal insight into the differences in economic worries caused by COVID-19 pandemic among individuals in a developing country context.